STEROID-RESISTANT EUTHYROID EXOPHTHALMOS, MYXEDEMA, AND OSTEOARTHROPATHY (EMO) SYNDROME TREATED WITH RITUXIMAB - Hernandez, Hernessa; Nicodemus, Nemencio (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Exophthalmos, pre-tibial myxedema, osteoarthropathy with acropachy (EMO/EMA) syndrome is a rare constellation of extra-thyroidal manifestations of Graves’ disease (GD) affecting less than one percent of this population. We present this case to describe the rare extrathyroidal manifestations of GD and share our experience with the use of rituximab. The case is a 57-year-old female, Filipino who was treated with total thyroidectomy for her Graves’ disease and developed post-surgical hypothyroidism replaced with levothyroxine. Three months after her surgery, she developed bilateral exophthalmos, followed by swelling of the interphalangeal joints, with digital clubbing (acropachy), and well-demarcated erythematous thickened plaques and nodules on both legs and feet (myxedema) and debilitating joint pains (osteoarthropathy). She was on high doses of steroids for almost ten years with no clinical improvement. Her thyroid function tests were normal but her TRAb assay was highly elevated. Her condition improved after treatment with rituximab and the steroid wasgradually tapered.